The Circadian Syndrome Predicts Lower Urinary Tract Symptoms Suggestive of Benign Prostatic Hyperplasia Better Than Metabolic Syndrome in Aging Males: A 4-Year Follow-Up Study - Xiong, Yang; Zhang, Fuxun; Wu, Changjing; Zhang, Yangchang; Huang, Xiaoyingzi; Qin, Feng; Yuan, Jiuhong (Frontiers in Medicine, 2021)
Background: The prevalence of lower urinary tract symptoms (LUTS) suggestive of benign prostate hyperplasia (BPH) increases in men. Although several risk factors, including metabolic syndrome (MetS) and depression, were identified, the underlying etiological factor remains unclear. Recently, circadian syndrome (CircS) was proposed as a novel risk cluster based on MetS. To compare the predictive power of the CircS and MetS for LUTS/BPH, this study was performed. Materials and Methods: In the baseline survey, 4,390 men older than 40 years from the China Health and Retirement Longitudinal Study were enrolled. Of them, 3,658 men were followed in the 2015 survey. Logistic regression was adopted to examine the relationships between CircS, MetS, and LUTS/BPH. To further verify the association, propensity score matching was used for sensitivity analyses. Moreover, the participants who had LUTS/BPH at the baseline were excluded to test the longitudinal relationships between CircS, MetS, and LUTS/BPH. In addition, we employed the receiver operating characteristic (ROC) curve analysis to compare the predictive power using the number of components of CircS and MetS. The DeLong test was used to test the disparities of area under the curves (AUCs). Results: The prevalence of CircS and MetS in aging men was 30.23 and 38.36%, respectively. The odds ratios for prevalent LUTS/BPH were 1.61 (95% CI = 1.29–2.00, P < 0.001) and 1.34 (95% CI = 1.08–1.66, P < 0.01), respectively, in aging men. This increased risk was also observed in incident LUTS/BPH. The prevalence of LUTS/BPH in normal, CircS alone, MetS alone, and both CircS and MetS groups was 6.96, 8.77, 7.83, and 10.77%, respectively. The AUCs for CircS predicting prevalent and incident LUTS/BPH were higher than those for MetS (0.582 vs. 0.556 for incident LUTS/BPH, P < 0.001; 0.574 vs. 0.561 for prevalent LUTS/BPH, P < 0.05). Conclusions: The CircS predicts both incident and prevalent LUTS/BPH better than MetS.